Bacterial , Cytological and Biochemical study of Arthritis in sheep ‎and goats .‎ - R. Nazaal, A.; M.H.AL-Judi , A.; A.Abdulla, F. (The Iraqi Journal of Veterinary Medicine, 2005)
Bacteriological , cytological, and biochemical testing were performed on synovial fluid of 160 sheep’s and goats at Basrah slaughter house , 115 sheep (74 females, 41 males ) , 45 goats (34 females , 11 males). The incidence of bacterial isolation from infected sheeps was 40.05 %. in females , 48.78 % . in males ,while in goats it was 54.54%. in males 14.7%. in females. Bacterial isolates were staphalococcus aureus, pseudomonas spp, and Hemophilus spp. Staph –aureus was senstive to impeneam and amikacin Hemophilus spp. was sensitive to cephalexin and Ampicillin , all Pseudomonas spp. isolates were sensitive to penicillin and amikacin. Mucin clot test varied from fair to poor clotting, the total protein of infected animals was significantly higher than that of control group. The total leucocytic count was significantly higher (p<0.01) than that of the control group, with high perecntage of Neutrophils.